Analysis of Shoe Upper Product Defect with the Seven Tools and Failure Mode and Effect Analysis (FMEA) Methods in PT. XYZ - Juniawan, Abdul Fattah; Sumiati, Sumiati (IJIEM - Indonesian Journal of Industrial Engineering and Management, 2024)
PT XYZ is a company engaged in the manufacturing industry with the production of shoe uppers. In the shoe upper production process, defects such as broken pulltab, mudguard crack, tilted backtab, and false collbar are still found which affect quality. The purpose of this study is to determine the level of defects that most often occur so that it can provide suggestions for improvement to reduce the defects of upper shoe products. The methods used are Seven Tools and Failure Mode and Effect Analysis (FMEA). Seven Tools include check sheets, statistics, histograms, pareto charts, pareto diagrams, scatter diagrams, control diagrams, and fishbone diagrams. Then proceed with FMEA analysis to get suggestions for corrective action. Based on the results of research on Seven Tools, it is known that the most dominant defect in shoe uppers is broken pulltab (38.4%), then mudguard crack (30.64%), tilted backtab (16.49%) and false collbar (14.47%). Based on the results of Failure Mode and Effect Analysis (FMEA) research, it is known that the cause of the highest problem at RPN 288 is unbalanced thread setting. The proposed improvement suggestion is to balance the upper thread tension and lower thread tension of the sewing machine.